Study on the Retention of Large Mining Height and Small Coal Pillar under Thick and Hard Roof of Bayangaole Coal - Shankun Zhao; Jianping Zuo; Lei Liu; Kaijun Wu (Advances in Civil Engineering)
The coal pillar stress distribution at the 311102 working face in the Bayangaole Mine is analyzed and revealed. In addition, borehole stressmeter, PASSAT monitoring system, and numerical modelling are fully utilized. Based on the patterns of acoustic wave velocity distribution, it is discovered that the impact created by mining activity can expand into the working face around 40 m, where the peak stress concentration is found about 15 m ahead. According to borehole stressmeter readings, mildly impacted, ordinarily impacted, and severely impacted zones are distinguished. The equilibrium theory and corresponding calculation indicated that the coal body in front of the working face has a plastic zone width of 4.96 m. The stress-displacement analysis based on numerical simulation showed that the relationship between peak vertical stress and pillar width is unimodal and bimodal. Specifically, both 5 and 10 m wide pillars showed a unimodal stress-width correlation and the peak vertical stresses are all located at the pillar center, whereas 15 m wide pillar has a bimodal stress-width relationship. In comparison, 10 m wide pillar holds the maximum in-situ stress. In consideration of site conditions and economic influences, 6 m wide coal strip coal pillar is designed at the working face 311102. As a result, stopping was successfully completed, and remarkable economic benefits were achieved.